Multilingual speech recognition for the elderly: The AALFred personal life assistant - Hämäläinen, A.; Teixeira, A.; Almeida, A. M. C.; Meinedo, H.; Fegyó, T.; Dias, J. (6th International Conference on Software Development and Technologies for Enhancing Accessibility and Fighting Info-exclusion, 2015)
The PaeLife project is a European industry-academia collaboration in the framework of the Ambient Assisted Living Joint Programme (AAL JP), with a goal of developing a multimodal, multilingual virtual personal life assistant to help senior citizens remain active and socially integrated. Speech is one of the key interaction modalities of AALFred, the Windows application developed in the project; the application can be controlled using speech input in four European languages: French, Hungarian, Polish and Portuguese. This paper briefly presents the personal life assistant and then focuses on the speech-related achievements of the project. These include the collection, transcription and annotation of large corpora of elderly speech, the development of automatic speech recognisers optimised for elderly speakers, a speech modality component that can easily be reused in other applications, and an automatic grammar translation service that allows for fast expansion of the automatic speech recognition functionality to new languages.